2016
DOI: 10.1051/0004-6361/201527450
|View full text |Cite
|
Sign up to set email alerts
|

Shape of the oxygen abundance profiles in CALIFA face-on spiral galaxies

Abstract: We measured the gas abundance profiles in a sample of 122 face-on spiral galaxies observed by the CALIFA survey and included all spaxels whose line emission was consistent with star formation. This type of analysis allowed us to improve the statistics with respect to previous studies, and to properly estimate the oxygen distribution across the entire disc to a distance of up to 3−4 disc effective radii (r e ). We confirm the results obtained from classical H  region analysis. In addition to the general negat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
214
5
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 174 publications
(261 citation statements)
references
References 199 publications
(298 reference statements)
39
214
5
3
Order By: Relevance
“…In Fig. 1 we demonstrate this fact by comparing our sample of galaxies with a well-defined sample presented in a previous work of the oxygen abundance radial distribution (Sánchez-Menguiano et al 2016b, hereafter SM16) based on the CALIFA survey (Calar Alto Legacy Integral Field Area Survey, Sánchez et al 2012a). We should note that the comparison sample was extracted from a well defined, statistically significant sample and representative of galaxies in the Local Universe (Walcher et al 2014).…”
Section: Data and Galaxy Samplesupporting
confidence: 57%
See 4 more Smart Citations
“…In Fig. 1 we demonstrate this fact by comparing our sample of galaxies with a well-defined sample presented in a previous work of the oxygen abundance radial distribution (Sánchez-Menguiano et al 2016b, hereafter SM16) based on the CALIFA survey (Calar Alto Legacy Integral Field Area Survey, Sánchez et al 2012a). We should note that the comparison sample was extracted from a well defined, statistically significant sample and representative of galaxies in the Local Universe (Walcher et al 2014).…”
Section: Data and Galaxy Samplesupporting
confidence: 57%
“…However, recently it has been found that some spiral galaxies show lower (higher) oxygen abundance val-ues in the inner (outer) regions than that expected according to the observed negative gradients. This results in a nearly flat distribution or even a drop towards the centre (Belley & Roy 1992;Rosales-Ortega et al 2011;Sánchez et al 2012bSánchez et al , 2014Sánchez-Menguiano et al 2016b;Zinchenko et al 2016), and an abundance flattening or even an increase in the outermost parts (Martin & Roy 1995;Vilchez & Esteban 1996;Roy & Walsh 1997;van Zee et al 1998;Rosales-Ortega et al 2011;Bresolin et al 2012;Marino et al 2012;López-Sánchez et al 2015;Sánchez-Menguiano et al 2016b;Belfiore et al 2017).…”
Section: The Shape Of the Abundance Profilesmentioning
confidence: 99%
See 3 more Smart Citations